Fibroblast Growth Factor 23 drives MMP13 expression in human osteoarthritic chondrocytes in a Klotho-independent manner. Issue 11 (November 2016) - Bianchi, A.; Guibert, M.; Cailotto, F.; Gasser, A.; Presle, N.; Mainard, D.; Netter, P.; Kempf, H.; Jouzeau, J.-Y.; Reboul, P.
Summary: Objective: Fibroblast Growth Factor 23 (FGF23) may represent an attractive candidate that could participate to the osteoarthritic (OA)-induced phenotype switch of chondrocytes. To address this hypothesis, we investigated the expression of FGF23, its receptors (FGFRs) and co-receptor (Klotho) in human cartilage and studied the effects of rhFGF23 on OA chondrocytes. Method: Gene expression or protein levels were analysed by RT-PCR and immunohistochemistry. Collagenase 3 (MMP13) activity was measured by a fluorescent assay. MAPK signalling pathways were investigated by phosphoprotein array, immunoblotting and the use of selective inhibitors. RNA silencing was performed to confirm the respective contribution of FGFR1 and Klotho. Results: We showed that the expression of FGF23, FGFR1 and Klotho was up-regulated at both mRNA and protein levels in OA chondrocytes when compared to healthy ones. These overexpressions were markedly elevated in the damaged regions of OA cartilage. When stimulated with rhFGF23, OA chondrocytes displayed an extended expression of FGF23 and of markers of hypertrophy such as MMP13, COL10A1, and VEGF. We demonstrated that FGF23 auto-stimulation was both FGFR1-and Klotho-dependent, whereas the expression of markers of hypertrophy was mainly dependent on FGFR1 alone. Finally, we showed that FGF23-induced MMP13 expression was strongly regulated by the MEK/ERK cascade and to a lesser extent, by the PI-3K/AKT pathway. Conclusion: These results demonstrate that FGF23 sustains differentiation of OA chondrocytes in a Klotho-independent manner.